1996
DOI: 10.1021/js950067y
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible To Estimate the Parameters of the Sigmoid Emax Model with Truncated Data Typical of Clinical Studies?

Abstract: Many drug concentration-effect relationships are described by the nonlinear sigmoid E(max) model. Clinical considerations frequently limit the magnitude of effect intensity that may be produced; the most pronounced effect intensity may be considerably below E(max). We have tested and quantified the influence of this limitation on the estimatability of the sigmoid E(max) model parameters. We have used the estimated parameter values to calculate data descriptors (drug concentrations required to produce certain e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 27 publications
1
38
3
Order By: Relevance
“…ͪ to the experimental data by weighted (1/y obs ) nonlinear regression (8). In this equation, the pharmacological effect E is the corresponding FT activity expressed as a percentage of baseline, E 0 is the effect when the C max is equal to 0, C 50 is the C max corresponding to 50% of the maximum effect, and is the sigmoidicity parameter.…”
Section: Resultsmentioning
confidence: 99%
“…ͪ to the experimental data by weighted (1/y obs ) nonlinear regression (8). In this equation, the pharmacological effect E is the corresponding FT activity expressed as a percentage of baseline, E 0 is the effect when the C max is equal to 0, C 50 is the C max corresponding to 50% of the maximum effect, and is the sigmoidicity parameter.…”
Section: Resultsmentioning
confidence: 99%
“…The PBMC cellular pellet was stored at À70jC until analysis. Farnesyltransferase activity was determined by a radioenzyme assay done by the Clinical Pharmacodynamics Laboratory at BristolMyers Squibb Pharmaceutical Research Institute, Three Hamilton Health Place, Hamilton, NJ, as previously described (25).…”
Section: Methodsmentioning
confidence: 99%
“…However, the concentrations were derived from sigmoid E max curve and pharmacokinetics was not considered. [14] The parameter estimation of sigmoid E max model is an important part in dose-finding study. Dragalin et al found that the adaptive designs with the selected dose applying Fisher information matrix were superior in finding target dose compared to the common designs with the doses allocated by equal interval.…”
Section: Transl Clin Pharmacolmentioning
confidence: 99%